Consumers' perception towards local herbal supplement products - Kamarulzaman, Nitty Hirawaty; Talib, S. M. (Institut Penyelidikan Perhutanan Malaysia, 2015)
Tongkat ali (Eurycoma longifolia), kacip fatimah (Labisia pumila), dukung anak (Phyllanthus niruri), misai kucing (Orthosiphon stamineus), and hempedu bumi (Andrographis paniculata) are some of the well-known local herbal food supplements. However, one of the biggest challenges for local herbal products is the lack of consumers’ interest in purchasing local herbs as their supplements. Although several wellness lifestyle campaigns emphasized on the use of local herbs in daily diet or health supplement, consumers’ awareness on its benefits were found still lacking. Thus, the purpose of the study was to determine consumers’ perception towards local herbal supplements. A face-to-face interview with 500 respondents in Klang Valley was carried out using a structured questionnaire. The data collected was analyzed using descriptive analysis, chi-square analysis, and factor analysis methods. The results indicated that majority of the respondents consumed local herbal products as supplement. Local herbs namely pegaga, tongkat ali, and kacip fatimah were the most preferred herbs consumed by majority of the respondents. Potential, awareness of negative effect, effectiveness, and suitability were the factors revealed to influence consumers’ perception towards local herbal supplement products. This study concluded that if consumers have a well-informed information on the potential and effectiveness of local herbal supplement products towards their health, it will improve their acceptance of herbal products.